Survival and biofilm formation by Group B streptococci in simulated vaginal fluid at different pHs - Borges, Sandra (2013)
The Group B Streptococcus (GBS, Streptococcus agalactiae) is an important cause of neonatal and maternal infection. GBS is a commensal organism of the lower gastrointestinal and vaginal tract. A frequent mode of neonatal infection is vertical transmission from pregnant women to their foetus or neonate. The aim of this study was to evaluate the survival and biofilm production of 10 GBS strains in simulated vaginal fluid at pH 4.2, 5.5 and 6.5. GBS survived longer at higher pH than at normal vaginal pH. At pH 4.2, with the exception of two isolates that were recovered up to 48 and 72 h, viable GBS numbers declined below the limit of detection by 24 h. At higher pH, GBS survived between 3 and 15 days. All isolates investigated were biofilm producers but biofilm production was greater in tryptone soy broth compared to simulated vaginal fluid. The quantity of biofilm produced increased with the rise in the pH. This study suggests that high vaginal pH may influence both GBS survival and biofilm production and thus could be a risk factor for GBS infection.